2020
DOI: 10.1002/ps.5750
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the venom protein components of the egg parasitoid Anastatus japonicus (Hymenoptera: Eupelmidae)

Abstract: BACKGROUND: Parasitoid venom is composed of a complex mixture of various active substances with different biological functions and is injected in the host during the parasitoid oviposition. Anastatus japonicus (Hymenoptera: Eupelmidae) is an egg parasite of Tessaratoma papillosa (Hemiptera: Tessaratomidae). Although the venom of this egg parasitoid plays an important role in the parasitic process, relatively little work has been done to address the mechanism.RESULTS: In the present study, proteomic analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…M. trabalae does not parasitize Hemiptera insects, but it is the dominant species parasitizing C. japonica eggs in the natural field [33]. It has been reported that A. japonicus has no parasitic factors other than the venom received in the reproductive organs [34]. Its venom gland is similar to that of the endoparasitic wasp Pteromalus puparum (Hymenoptera: Pteromalidae) [35], and the venom of P. puparum has been reported to cause significant changes in the total number of host blood cells, disrupt the cytoskeleton, alter the behavior of blood cells such as stretching, adsorption, and aggregation, and affect the cystic host response to parasitoid eggs, thereby suppressing host cellular immunity [36].…”
Section: Introductionmentioning
confidence: 99%
“…M. trabalae does not parasitize Hemiptera insects, but it is the dominant species parasitizing C. japonica eggs in the natural field [33]. It has been reported that A. japonicus has no parasitic factors other than the venom received in the reproductive organs [34]. Its venom gland is similar to that of the endoparasitic wasp Pteromalus puparum (Hymenoptera: Pteromalidae) [35], and the venom of P. puparum has been reported to cause significant changes in the total number of host blood cells, disrupt the cytoskeleton, alter the behavior of blood cells such as stretching, adsorption, and aggregation, and affect the cystic host response to parasitoid eggs, thereby suppressing host cellular immunity [36].…”
Section: Introductionmentioning
confidence: 99%
“…Hexamerins may also bind to natural organic compounds such as riboflavin (vitamin B2) (Magee et al, 1994), ecdysteroids (Enderle et al, 1983), and juvenile hormone (Braun and Wyatt, 1996). In addition, hexamerins have been shown to be part of the venom protein phase in the parasitoid wasp Anastatus japonicus (Wang et al, 2020) and the honeybee A. mellifera (Hoffman, 2006), as well as being associated with phase transition, solitary to gregarious, in Locusta migratoria (Kang et al, 2004). Because of their high heritability, hexamerins have also been linked to insects' reproductive and dispersal capacities, underlying the evolutionary use of fragmented landscapes (Somervuo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%